Salt-Tolerant Halophyte Rhizosphere Bacteria Stimulate Growth of Alfalfa in Salty Soil - Kearl, Jennifer; McNary, Caitlyn; Lowman, J. Scott; Mei, Chuansheng; Aanderud, Zachary T.; Smith, Steven T.; West, Jason; Colton, Emily; Hamson, Michelle; Nielsen, Brent L. (Frontiers in Microbiology, 2019)
Halophytes are plants that have adapted to grow in saline soils. Many halophyte species from around the world have been studied, but little is known about the microbiomes associated with these plants. Bacteria were isolated from the rhizosphere and as root endophytes associated with Salicornia rubra, Sarcocornia utahensis, and Allenrolfea occidentalis, three native Utah halophytes. 16S rRNA gene sequencing analysis of the bacterial isolates identified species from several genera, including Halomonas, Bacillus, Kushneria, Virgibacillus, Planococcus, Pseudomonas, and others. Each isolate was tested for maximum salt tolerance, and some were able to grow in the presence of up to 3 M or 4 M NaCl. Pigmentation, Gram stain characteristics, optimal temperature for growth, and biofilm formation analysis were used to aid in identification of the species. Soil and root samples were also analyzed for non-culturable bacterial species by Illumina DNA sequencing. The most commonly identified bacteria from this analysis were members of the following phyla: Acidobacteria, Actinobacteria, Bacteroidetes, Chloroflexi, and Gamma- and Delta-Proteobacteria. Members of these phyla are commonly found in soil or in extreme environments. While there is some variation in the bacterial population in samples collected at different times of the year, Halomonas and Kushneria species were consistently isolated both from the soil and as endophytes from plant roots in all collections. Several isolates were tested for the ability to stimulate growth of alfalfa under saline conditions. We identified Halomonas and Planococcus isolates that, when used to inoculate young seedlings, stimulate plant growth in the presence of 1% NaCl, a concentration that significantly inhibits growth and development of uninoculated alfalfa. Halomonas was recovered from surface sterilized roots of inoculated alfalfa plants, indicating the ability of the inoculum to become established as an endophyte. These isolates, when used as an inoculum, thus have significant promise for enhancing growth of alfalfa in salty soil.